A Milling Method for Elliptic-arc-tooth-trace Cylindrical Gear - Zhao Kunpeng; Song Aiping; Dou Chaoran; Zi Hao Chu; Yuegang (Jixie chuandong)
On the basis of the study on the circular-arc-tooth-trace cylindrical gear,the milling method of the elliptic-arc-tooth-trace cylindrical gear which can realize whole teeth width meshing is proposed. By analyzing the ideal geometric parameters,the equations of tooth surface and contact ratio are deduced. The forming processes of the machining tools and elliptic-arc-tooth-trace are analyzed by the rack and pinion model,and the milling principle is put forward according to which the milling of the gear is completed. The profiles of the gear machined by the oblique mounting tools are all involute in the radial sections,and the expansion curve of the tooth trace on the reference cylindrical surface is part of the ellipse. The convex and the concave tooth trace have the same geometric parameters. The processing principle can completes the high-efficiency milling of the gear,and also can be used for grinding.